Polyamino acid enhancement of bacterial phagocytosis by human polymorphonuclear leukocytes and peritoneal macrophages. - Peterson, P K (1984)
Cationic polyamino acids are known to enhance a variety of cell-cell interactions by virtue of their ability to alter electrostatic forces of cell surfaces. In this study, the effect of polyamino acids on phagocytosis of 3H-labeled bacteria by human polymorphonuclear leukocytes (PMNs) and peritoneal macrophages was investigated. Negatively charged and neutral polyamino acids did not influence phagocytosis of unopsonized Staphylococcus epidermidis, whereas protamine, poly-L-arginine, and poly-L-lysine stimulated phagocytosis in a dose-dependent manner. At 50 micrograms/ml, greater than 30% uptake by PMNs was seen with each of these cationic polyamino acids. Although cationic polyamino acids promoted PMN and peritoneal macrophage phagocytosis of unopsonized S. epidermidis, Staphylococcus aureus M (encapsulated) and M variant (unencapsulated), and Escherichia coli J5, little effect was seen with the parent E. coli O111:B4 or a serotype O222:H16 strain. Pretreatment of bacteria and phagocytes separately demonstrated that the phagocytosis-promoting property of polyamino acids is manifest predominantly on the bacteria. Bacteria pretreated with cationic polyamino acids also elicited a PMN chemiluminescent response, and PMN-associated bacteria were killed, as determined by a fluorochrome microassay. Thus, cationic polyamino acids promote the phagocytosis and killing of many but not all bacterial strains, and in this respect polyamino acids function as opsonins.